2023
DOI: 10.1108/jpbafm-01-2023-0005
|View full text |Cite
|
Sign up to set email alerts
|

Mayor re-election and earnings management: evidence from Portuguese municipalities

Augusta Ferreira

Abstract: PurposeThe aim of this paper is to investigate whether Mayors in Portugal engage in earnings management close to zero with the motivation of re-election.Design/methodology/approachThe data used in this study were annual financial information from Portuguese municipalities from 2005 to 2016, as well as data on elections and Mayor re-elections involving three political cycles. The methodologies employed were quantitative, including graphical and panel data regressions.FindingsThe results indicate that municipali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This article offers a valid contribution to the earnings management literature as it is the first study investigating budget execution items. It is also noteworthy in that it provides evidence of the role of political factors, similar to the work of Ferreira (2024), along with additional variables linked to the financial sustainability of municipalities.…”
Section: Earnings Management Research In Public Sector Organizations:...mentioning
confidence: 91%
See 2 more Smart Citations
“…This article offers a valid contribution to the earnings management literature as it is the first study investigating budget execution items. It is also noteworthy in that it provides evidence of the role of political factors, similar to the work of Ferreira (2024), along with additional variables linked to the financial sustainability of municipalities.…”
Section: Earnings Management Research In Public Sector Organizations:...mentioning
confidence: 91%
“…Previous research on this topic at the local government level is confined to a study by Cohen et al (2019), which showed that there is an inclination in Greek municipalities to engage in earnings management the year before the election year and that, when the mayor of a municipality is re-elected, earnings management is higher, ceteris paribus, in comparison with that in municipalities where the mayor is elected for the first time. The work by Ferreira (2024) is based on a sizable sample of Portuguese municipalities for the period 2005-2016, covering three election cycles. As her point of departure, Ferreira utilizes the Jones model (Jones, 1991) to estimate discretionary accruals and the distribution approach developed by Burgstahler and Dichev (1997) Financial Management management, with this behavior becoming more pronounced in pre-election years.…”
Section: Earnings Management Research In Public Sector Organizations:...mentioning
confidence: 99%
See 1 more Smart Citation